The impact of the standardization of the NPD process on its efficiency - Karničar Šenk, Mateja; Roblek, Matjaž (Journal of Business Economics and Management, 2019)
The purpose of this study is to examine the impact of the standardization of the new product development (NPD) process on its efficiency. A dilemma exists with regard to determining to what extent NPD processes should be standardized, in order to not hinder the operators during the performance of NPD process and consequently, weaken it. The case analysis for this study was carried out at a company whose process development has been standardized for a decade and has undergone several degrees of standardization. Quantitative and qualitative research methods were applied in the study. A regression method was used for quantitative research in order to study the effects of selected dependent and independent variables; using qualitative analysis, we supported the findings of the quantitative analysis. The results of the analysis indicate that the standardization of the NPD process does have an impact on its efficiency. From the obtained results, it may also be concluded that a very high degree of standardization begins to reduce the efficiency of the NPD process.